2017
DOI: 10.1038/onc.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ADAM-9 in HGF/CDK4 mice impairs melanoma development and metastasis

Abstract: ADAM-9 is a metalloproteinase expressed in peritumoral areas by invading melanoma cells and by adjacent peritumoral stromal cells; however, its function in stromal and melanoma cells is not fully understood. To address this question in vivo in a spontaneous melanoma model, we deleted ADAM-9 in mice carrying the hepatocyte growth factor (Hgf) transgene and knock-in mutation Cdk4, demonstrated to spontaneously develop melanoma. Spontaneous melanoma arose less frequently in ADAM-9-deleted mice than in controls. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…B), suggesting an integrin‐independent impact of ADAM9 on adhesion to these ECM substrates. Our results indicate a role of ADAM9 in mediating cell–matrix interactions and corroborate findings from earlier studies (Cominetti et al ., ; Giebeler et al ., ; Mygind et al ., ; Zigrino et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…B), suggesting an integrin‐independent impact of ADAM9 on adhesion to these ECM substrates. Our results indicate a role of ADAM9 in mediating cell–matrix interactions and corroborate findings from earlier studies (Cominetti et al ., ; Giebeler et al ., ; Mygind et al ., ; Zigrino et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Functional studies focusing on the role of ADAM9 in tumor biology are scarce. In the murine HGF/CDK4 melanoma model, ADAM9 contributes to tumor formation and metastatic load (Giebeler et al ., ). That study also highlighted a pivotal role of ADAM9 in trans‐endothelial migration, which was corroborated by other studies (English et al ., ; Micocci et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that ADAM9 regulates cell–cell and cell–matrix interaction by binding to integrins, thereby leading to modulation of protease secretion and cell migration [ 11 , 12 , 13 ]. ADAM9 expression in melanoma cells contributes to melanoma progression modulating cell adhesion to the endothelium and altering basement membrane (BM) integrity by proteolytically processing the laminin-beta3 chain [ 14 ]. On the other hand, ADAM9 is found to be highly expressed in peritumoral areas where activated fibroblasts are found [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADAM9 expression in melanoma cells contributes to melanoma progression modulating cell adhesion to the endothelium and altering basement membrane (BM) integrity by proteolytically processing the laminin-beta3 chain [ 14 ]. On the other hand, ADAM9 is found to be highly expressed in peritumoral areas where activated fibroblasts are found [ 14 , 15 ]. In these cells, altered expression of ADAM9 controls TIMP-1 expression and TNF-α/sTNFR1 pathway leads to modulation of melanoma cells proliferation and apoptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%